Selection of methods for the evaluation of available soil copper - Cruz, Mara Cristina Pessôa da; Ferreira, Manoel Evaristo (Pesquisa Agropecuaria Brasileira, 2014)
The purpose of this study was to evaluate various extractants for predicting available copper in soils. Thirty surface soil samples representing five great soil groups ("Solos Podzolizados de Lins e Marília variação Lins" and "variação Marília", "Latossolo Vermelho-Escuro, fase arenosa", "Latossolo Roxo" and "Terra Roxa Estruturada") were gathered from fields in Jaboticabal, SP, Brazil, and corn (Zea mays, L.) was used as indicator plant in a greenhouse experiment. Available copper concentration in each soil sample was determined by the following extracting solutions: 0.5 M CaCl2, 2.0 N MgCl2, 1,0 N CH3COONH 4 adjusted at pH 6.0 and 4.8, 0.05 and 0.1 N HCl, 0.05 N H2SO4 , 0,035 M DTPA pH 7.3 and pH 6.0, 0.01 M EDTA + 1.0 M (NH4)2CO3 (pH 8.6) and 0.02 M EDTA + 0.5 M CH3C00H + 0.5 M CH3COONH4 (AAAc-EDTA pH 4.65) and Na2EDTA 1%. The best method was chosen with the helps of correlation and regression coefficients between the soil copper extracted from the different procedures and that one absorbed by the plant. With exception to 0.5 M CaCl2, all extractants gave significant and well near correlation coefficients. Also by using variation and angular coefficients and the easiness of the method one of the follow extractants can be indicated to evaluate the available soil copper: 0.005 M DTPA pH 7.3, 0.1 N HCl and 1.0% Na2EDTA